2008
DOI: 10.1007/s00428-008-0647-0
|View full text |Cite
|
Sign up to set email alerts
|

What is the significance of CD34 immunostaining in the extraglomerular and intraglomerular mesangium?

Abstract: CD34, traditionally a marker of hematopoietic stem cells (HSCs), was found on endothelial cells and fibroblasts as well. At the level of the extraglomerular or intraglomerular mesangium, CD34 may signal either the presence of HSCs or, conversely, may be a marker of transdifferentiation. CD34-positive cells of the extraglomerular mesangium could migrate into the intraglomerular mesangium and participate in reparative processes at this level. The aim of our study was to analyze the presence of CD34 at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…8A and 8B) [64]. Alternatively, Gluhovschi et al indicated CD34 does not significantly correlate with mesangial α-SMA [19]. Swimming exercise at 60 min program restored its level to normal (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…8A and 8B) [64]. Alternatively, Gluhovschi et al indicated CD34 does not significantly correlate with mesangial α-SMA [19]. Swimming exercise at 60 min program restored its level to normal (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…At the level of extraglomerular or intraglomerular mesangium, CD34 may signal either the presence of HSCs, or conversely, may be a marker of transdifferentiation [19]. Immunohistochemical co-staining of CD34 and α-SMA has been used to study various glomerulonephritis (GN) as a transformed mesangial cell marker [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better quantify the histological lesions, a scoring system adapted from Neumann [15] was employed on kidney biopsies. We used this scoring system in two previous reports [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In one of our previous studies we have analyzed the presence of CD34 at the level of the extraglomerular mesangium, concluding that it could be either a marker of stem cells entering the glomerulus at this level or a marker of mesangial activation [9].…”
Section: Cd34-positive Fibroblast-like Cells In Glomerulonephritismentioning
confidence: 99%